2021
DOI: 10.1108/ijlm-08-2020-0339
|View full text |Cite
|
Sign up to set email alerts
|

Supplier performance measurement system use, relationship trust, and performance improvement: a dyadic perspective

Abstract: PurposeGrounding on resource orchestration theory, this paper aims to study the relationship between the way buying companies use their supplier performance measurement systems and the performance improvements obtained from suppliers, with relationship trust identified as a mediator in the previous link.Design/methodology/approachThe authors design a conceptual model and test it through structural equation modelling on a final sample of 147 buyer-supplier responses, collected by means of a dyadic survey.Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Johnston et al (2004) revealed that the level of a supplier trust regarding a buyer enhances innovation, quality, long-term and short-term costs, and buyer satisfaction. Thus, confidence in a partner's capabilities and commitment are key enablers to NPD speed and quality improvement (Kabadurmus, 2020;Maestrini et al, 2021).…”
Section: Social Assets For Npd Involving Suppliersmentioning
confidence: 99%
See 3 more Smart Citations
“…Johnston et al (2004) revealed that the level of a supplier trust regarding a buyer enhances innovation, quality, long-term and short-term costs, and buyer satisfaction. Thus, confidence in a partner's capabilities and commitment are key enablers to NPD speed and quality improvement (Kabadurmus, 2020;Maestrini et al, 2021).…”
Section: Social Assets For Npd Involving Suppliersmentioning
confidence: 99%
“…Parties evaluate outcomes obtained from a particular exchange relationship in order to determine their commitment to this relationship or to the partners it entails (Schiele et al ., 2012). They qualify these outcomes by relying on present and past experience with comparable relationships and knowledge of the other party's similar partnerships (Maestrini et al ., 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, although the literature is establishing the importance of supply chain resources on product launch performance, additional theory suggests that product launches may also be impacted by the manner in which organizations utilize these and other resources. Specifically, resource orchestration theory (ROT) highlights the importance of managerial actions in creating competitive advantage (Maestrini et al ., 2021), proposing that the managerial use of resources is a key differentiator of competitive advantage. Recent meta-analytic evidence (dslb) confirms these inferences, finding that the “resources a firm possesses and the actions it takes to use them are jointly important determinants of performance advantages” (p. 1385).…”
Section: Introductionmentioning
confidence: 99%